Quantitative and Discrete Evolutionary Changes in the Egg-Laying Behavior of Single Drosophila Females - Bräcker, Lasse B.; Schmid, Christian A.; Bolini, Verena A.; Holz, Claudia A.; Prud’homme, Benjamin; Sirota, Anton; Gompel, Nicolas (Frontiers in Behavioral Neuroscience, 2019)
How a nervous system assembles and coordinates a suite of elementary behavioral steps into a complex behavior is not well understood. While often presented as a stereotyped sequence of events, even extensively studied behaviors such as fly courtship are rarely a strict repetition of the same steps in a predetermined sequence in time. We are focusing on oviposition, the act of laying an egg, in flies of the genus Drosophila to describe the elementary behavioral steps or microbehaviors that a single female fly undertakes prior to and during egg laying. We have analysed the hierarchy and relationships in time of these microbehaviors in 3 closely related Drosophila species with divergent egg-laying preferences, and uncovered cryptic differences in their behavioral patterns. Using high-speed imaging, we quantified in depth the oviposition behavior of single females of Drosophila suzukii, Drosophila biarmipes and Drosophila melanogaster in a novel behavioral assay. By computing transitions between microbehaviors, we identified a common ethogram structure underlying oviposition of all three species. Quantifying parameters such as relative time spent on a microbehavior and its average duration, however, revealed clear differences between species. In addition, we examined the temporal dynamics and probability of transitions to different microbehaviors relative to a central event of oviposition, ovipositor contact. Although the quantitative analysis highlights behavioral variability across flies, it reveals some interesting trends for each species in the mode of substrate sampling, as well as possible evolutionary differences. Larger dataset derived from automated video annotation will overcome this paucity of data in the future, and use the same framework to reappraise these observed differences. Our study reveals a common architecture to the oviposition ethogram of 3 Drosophila species, indicating its ancestral state. It also indicates that Drosophila suzukii's behavior departs quantitatively and qualitatively from that of the outgroup species, in line with its known divergent ethology. Together, our results illustrate how a global shift in ethology breaks down in the quantitative reorganization of the elementary steps underlying a complex behavior.